YKL-40, soluble IL-2 receptor, angiotensin converting enzyme and C-reactive protein: Comparison of markers of sarcoidosis activity - Uysal, Pelin; Durmuş, Sinem; Sözer, Volkan; Gelişgen, Remise; Seyhan, Ekrem Cengiz; Erdenen, Füsun; Şimşek, Gönül; Uzun, Hafize (MDPI, 2018)
The aims of this study were to describe the clinical, radiological and immunological features of a population of sarcoidosis patients and to analyse chitinase-3-like protein 1 (YKL-40), soluble interleukin-2 receptor (sIL-2R), neopterin concentrations and adenosine deaminase (ADA) activity in serum of these patients in order to understand their potential as disease markers. Fifty-nine patients affected by chronic sarcoidosis, in active (20 patients) and inactive (39 patients) phase according to the clinical, radiological and laboratory criteria were studied. Serum YKL-40, sIL-2R, high-sensitive C-reactive protein (hs-CRP), neopterin levels and ADA activities were evaluated and compared with those of 25 healthy controls. Individuals with chronic sarcoidosis were significantly higher serum YKL-40, sIL-2R, neopterin, hs-CRP concentrations, angiotensin converting enzyme (ACE) and ADA activity than those of control subjects. Sarcoidosis patients in the active phase of the disease were significantly higher YKL-40, sIL-2R, hs-CRP levels and ACE activity than those in the inactive phase, while ADA activities and neopterin levels did not display any significant difference between the active and inactive disease groups. In comparison to the other parameters, as panel measurement of the serum YKL-40, sIL-2R, ACE and hs-CRP indicate a greater discrimination between active and inactive disease. The results indicate that serum YKL-40, sIL-2R, ACE and hs-CRP concentrations may be useful marker for monitoring sarcoidosis disease activity.
WOS: 000448394900042
PubMed ID: 30154391
Keywords: Sarcoidosis; Chitinase 3 Like Protein 1 (YKL-40); Soluble Interleukin 2 Receptor (sIL-2R); High Sensitive C-Reactive Protein (hs-CRP); Adenosine Deaminase (ADA); Angiotensin Converting Enzyme (ACE); Neopterin (NEO)